International High-Risk Clones Among Extended-Spectrum β-Lactamase–Producing Escherichia coli in Dhaka, Bangladesh - Mazumder, Razib; Hussain, Arif; Abdullah, Ahmed; Islam, Md. Nazrul; Sadique, Md. Tuhin; Muniruzzaman, S. M.; Tabassum, Anika; Halim, Farhana; Akter, Nasrin; Ahmed, Dilruba; Mondal, Dinesh (Frontiers in Microbiology, 2021)
Background:Escherichia coli is a major extended-spectrum β-lactamase (ESBL)–producing organism responsible for the rapid spread of antimicrobial resistance (AMR) that has compromised our ability to treat infections. Baseline data on population structure, virulence, and resistance mechanisms in E. coli lineages from developing countries such as Bangladesh are lacking. Methods: Whole-genome sequencing was performed for 46 ESBL–E. coli isolates cultured from patient samples at the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b)-Dhaka. Sequence data were analyzed to glean details of AMR, virulence, and phylogenetic and molecular markers of E. coli lineages. Results: Genome comparison revealed presence of all major high-risk clones including sequence type 131 (ST131) (46%), ST405 (13%), ST648 (7%), ST410 (4.3%), ST38 (2%), ST73 (2%), and ST1193 (2%). The predominant ESBL gene and plasmid combination were blaCTX–M–15 and FII-FIA-FIB detected in diverse E. coli phylogroups and STs. The blaNDM–5 (9%) gene was present in prominent E. coli STs. One (2%) mcr-1–positive ST1011 E. coli, coharboring blaCTXM–55 gene, was detected. The extraintestinal pathogenic E. coli genotype was associated with specific E. coli lineages. The single nucleotide polymorphism (SNP)-based genome phylogeny largely showed correlation with phylogroups, serogroups, and fimH types. Majority of these isolates were susceptible to amikacin (93%), imipenem (93%), and nitrofurantoin (83%). Conclusion: Our study reveals a high diversity of E. coli lineages among ESBL-producing E. coli from Dhaka. This study suggests ongoing circulation of ST131 and all major non-ST131 high-risk clones that are strongly associated with cephalosporin resistance and virulence genes. These findings warrant prospective monitoring of high-risk clones, which would otherwise worsen the AMR crises.